Utilization of Physiotherapy in the continuum of stroke care at a tertiary hospital in Ibadan, Nigeria (2017)
Objectives: To investigate the pattern of referral for and utilisation of physiotherapy in the continuum of stroke care at a tertiary hospital in Ibadan, Nigeria. Methods: Referral notes and medical records of patients admitted in the University College Hospital, Ibadan with a clinical diagnosis of stroke between January, 2009 and December, 2013 were retrospectively reviewed. Information on age, sex, type of stroke, length of hospital stay, referral for physiotherapy and utilisation of physiotherapy were retrieved. Data were summarised using descriptive statistics and analysed using Chi-square test. Results: A total of 783 patients with stroke were admitted in the hospital during the period under study. The in-patient mortal ity rate was 37.2%. The mean Length of Hospital Stay (LoHS) was 16.17±12.34 days. Referral rate for physiotherapy was high (75.8%) and the mean time from admission to referral for physiotherapy was three days. Majority of patients referred utilised physiotherapy (63.4%) and mean number of physiotherapy sessions received during in-patient care was 8.69±6.45. There was a significant association between LoHS and utilisation of in-patient physiotherapy (p=0.02). Conclusion: The referral rate of stroke patients for physiotherapy was relatively high. Utilisation of in-patient physiotherapy reduced length of hospital stay among patients with stroke. Utilisation of out-patient physiotherapy was low. Strategies to enhance out-patient utilisation should be explored.